INTERNACIONALIZAÇÃO = EMI? EVIDÊNCIAS DO INGLÊS NA UFES - Taquini, Reninni (2020)
This study aims to reflect on the role of foreign/additional languages (L2) in the process of internationalization of higher education. To this end, the study analyzes the role of L2 in general and English in particular in the process of internationalizat